Aging resistance of surface-treated dental zirconia. Issue 2 (February 2015) - Inokoshi, Masanao; Vanmeensel, Kim; Zhang, Fei; De Munck, Jan; Eliades, George; Minakuchi, Shunsuke; Naert, Ignace; Van Meerbeek, Bart; Vleugels, Jozef
Highlights We assess the rough polished, Al2O3 or tribochemical silica sandblasted zirconia. These surface treatments improve the aging resistance of Y-TZP zirconia. Ce-TZP/Al2O3 zirconia are not affected by low-temperature degradation. Surface treatments slightly decrease the aging resistance of Y-TZP/Al2O3 zirconia.